2019
DOI: 10.1109/jlt.2019.2922397
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Fano Resonance for Flat-Top Broadband Reflectors Based on Single Guided-Mode Resonance

Abstract: We investigated on the interaction between a single guided-mode resonance and Fabry-Perot resonance (FPR) in a high contrast grating (HCG) from a viewpoint of Fano resonance. It has been found that the background reflection due to the FPR in the HCG is useful to implement flat-top broadband reflectors via tailoring the phase polarity of Fano resonance. The novel conceptual approach was elucidated theoretically with the temporal coupledmode theory (TCMT), which was confirmed by the Si HCG broadband reflector de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In this paper, it is revealed that the controlling of surface EM waves can be achieved by simply changing the depth or refractive index of a single deep subwavelength groove in the metal grating, and detailed physical explanation is given. With the increase of the groove depth or refractive index, the surface wave propagation characteristics show obvious periodic changes, which is essentially caused by the mode resonance between the surface modes and the groove cavity modes, similar to the Fano resonance [47][48][49][50] . Moreover, under the mode resonance, the grating surface will form high-intensity local standing waves, which can be applied to deep subwavelength resonators or spasers.…”
Section: Surface Wave Manipulation By Plasmonic Metasurface Based On mentioning
confidence: 99%
“…In this paper, it is revealed that the controlling of surface EM waves can be achieved by simply changing the depth or refractive index of a single deep subwavelength groove in the metal grating, and detailed physical explanation is given. With the increase of the groove depth or refractive index, the surface wave propagation characteristics show obvious periodic changes, which is essentially caused by the mode resonance between the surface modes and the groove cavity modes, similar to the Fano resonance [47][48][49][50] . Moreover, under the mode resonance, the grating surface will form high-intensity local standing waves, which can be applied to deep subwavelength resonators or spasers.…”
Section: Surface Wave Manipulation By Plasmonic Metasurface Based On mentioning
confidence: 99%
“…The existence of the partial reflectivity in the channel results in a non-zero mutual coupling coefficient as discussed in Appendix, and = 0 occurs when = (m is an integer.) [4,5]. When = 0 is assumed, from (4) and ( 5), the coupling coefficients of each mode into the respective ports are related as Substituting ( 6) into (3), we obtain…”
Section: Theoretical Description Of the Unidirectional Emittermentioning
confidence: 99%
“…In addition, the background scattering itself should satisfy the resonant condition ( = 0 or = 1) at the resonant frequency of those two modes. In the design of the structure, we first designed a broadband reflector of ~ 100 % peak reflectivity based on the interaction between a relatively low quality factor (~ 10) GMR mode and the background scattering, where ~ 100 % peak reflectivity verifies the coincidence of the resonance frequencies of the low quality factor GMR mode and the background scattering [5]. Then, the structure is further optimized to make the resonant frequency of another GMR mode of a relatively high quality factor (> ~ 1000) coincide with the peak reflectivity frequency of the broadband reflector.…”
Section: Design Of Unidirectional Emittermentioning
confidence: 99%
See 2 more Smart Citations